1988
DOI: 10.1136/adc.63.10.1184
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emission computed tomography in seizure disorders.

Abstract: SUMMARY Fourteen children with various seizure disorders were studied using a cerebral blood flow tracer, 123I iodoamphetamine (0.05 mCi/kg), and single photon emission computed tomography (SPECT). In the five patients with radiological lesions, SPECT showed congruent or more extensive abnormalities. Five of the nine children with a normal scan on computed tomography had abnormal SPECT studies consisting of focal hypoperfusion, diffuse hemispheric hypoperfusion, multifocal and bilateral hypoperfusion, or focal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Aseries of children with primarily generalised epilepsy is currently being investigated after injeetion of 99mTc-HM-PAO during photostimulation and hyperventilation. Promising results of SPECT in neonatal brain impairments have been published (7,12) and were achieved in the present study. Besides congruent findings with CT and ultrasound of structural lesions and periventricular leucomalacias, parasagittallesions, seen mainly in term infants (29), and other corticallesions were indicated.…”
Section: Diseussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Aseries of children with primarily generalised epilepsy is currently being investigated after injeetion of 99mTc-HM-PAO during photostimulation and hyperventilation. Promising results of SPECT in neonatal brain impairments have been published (7,12) and were achieved in the present study. Besides congruent findings with CT and ultrasound of structural lesions and periventricular leucomalacias, parasagittallesions, seen mainly in term infants (29), and other corticallesions were indicated.…”
Section: Diseussionsupporting
confidence: 66%
“…The role of SPECT in the preoperative evaluation before epilepsy surgery has already been established (20,25). Promising reports have also recently emerged on the usefulness of SPECT for exploring neurological impairments other than epilepsy (19,28) ranging from ischemic brain lesions in the newbom (7) to dementia in the old (17).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of SPECT in children with epilepsy have been mostly interictal and have investigated children with a variety of epilepsy syndromes (Denays et al, 1988; Chiron et al, 1989; Iivanainen et al, 1990; O'Tauma et al, 1990O'Tauma et al, , 1991; Vles et al, 1990; Uvebrant et al, 1991;Adams et al, 1992). Detailed study of ictal SPECT in children with partial epilepsy has not been reported.…”
mentioning
confidence: 99%
“…1990) and children (Denays et al 1988;Gelfand and Stowens 1989;Ivanainen et al 1990) with seizure disorders. The EEG may not be able to assess the extent and severity of the underlying cerebral involvement and may have difficulty in localizing the origin of the seizure due to its limited spatial resolution.…”
Section: Discussionmentioning
confidence: 99%